CCTV Architectural Design for Theft Detection using Intruder Detection System - Kembuan, Eddy D.R.E; Batmetan, Johan Reimon; Daud, Metsi; Tarandung, Iszach R P (JR Education, 2022)
The human need for a monitoring system for certain places is increasing. In this regard, the computer laboratory belonging to the school is not free from security intruders. Security bully or in English is usually called